Variação sazonal no óleo essencial e densidade de tricomas de acessos de erva-baleeira (Varronia curassavica Jacq.) - Thaise Ohana Moura Fernandes (2017)
Varronia curassavica is a Brazilian species with medicinal anti-inflammatory action by -humulene and -caryophyllene compounds of the essential oil. The objective of this work was to evaluate the seasonality in the chemical composition and in the essential oils content and the density of glandular trichomes present in the leaves of the accesses of V. curassavica. The leaves were collected, monthly, during 12 months, of six accesses (ICA VC1, ICA VC2, ICA VC3, ICA VC4, ICA VC5 and ICA VC6) at the whiting Germplasm Bank of the ICA/UFMG for the extracting and determining the essential oil content. The essential oils were analyzed by gas chromatography coupled to mass spectrometry (GC-MS) for identification of the compounds. The meteorological data were collected from the National Institute of Meteorology (INMET) for correlation with the essential oil content. For the counting of glandular trichomes, leaves of the same accessions were collected at 7h, on the day of the beginning of the analysis. The samples were clarified and the density evaluated on the abaxial and adaxial surfaces under light microscopy. The data were analyzed by descriptive statistical analysis (chemical composition), correlation (meteorological variables with essential oil content) and medium test (density of trichomes and essential oil content). The month with the highest average annual essential oil content was July 2014 and the access with the highest mean and stability was the ICA VC3. Significant correlations were observed oil content with relative humidity in the access ICAVC2 e ICA VC4. A total of 46 chemical compounds were detected in the essential oils and, in all accesses, the chemical markers of the species, -humulene and -caryophyllene were detected, in addition to -bourbonene, -elemeno, spatulenol, germacrene and oxide of caryophyllene. Only ICA-VC5 did not present an average abundance of -humulene greater than 2,6%. The accesses ICA VC4, ICA VC5 and ICA VC6 had higher averages of trichomes in the abaxial face than the accesses ICA VC1, ICA VC2 and ICA VC3 and the accesses ICA VC3, ICA VC4 and ICA VC6 had averages higher than the accesses ICA VC2 and ICA VC5, with averages higher than the accesses ICA VC1 in the adaxial face. The results indicate that seasonality influences the content and chemical composition of essential oils, as both vary throughout the year. The most suitable access for future studies is the ICA - VC3 because it presents a higher stability and average for the essential oil content and for maintaining the average annual abundance of - humulene higher than 2,6%. From the density of glandular trichomes observed, it is possible to infer that there is genetic variability among the accesses.